Queen of the universe a novel - Wurtzbach, Pia Alonzo (Tuttle Publishing, 2023)
Cleo is young, beautiful, talented and--until lately--lucky in love. But in the cut-throat world of international beauty competitions, she has to make the biggest decision of her life. She passionately wants to see how far she can go and what she can achieve. And to prove her estranged film director father that his family has done better than just survive without him. Her road is riddled with frustrations, dashed hopes and the age-old question--what is the price of fame and fortune?As the competition heats up, Cleo must navigate the dirty tricks contestants use to turn the odds in their favor. And ultimately, she must ask herself: How much is her own integrity worth?Set against the rich backdrop of Manila's glittering urban life, Queen of the Universe is about remembering who you are in the dizzying world of beauty contests and celebrity, told by an international influencer, model, actress and former Miss Universe.-- Back cover.